Analysis Of The Influence Of Motivation and Job Satisfaction On Employee Performance With Length Of Work As An Intervening Variable: Study At PT. Coca Cola Amatil Indonesia (Central Java) - Koen Irianto Uripan; Angga Martha Mahendra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Study This aim For analyze influence motivation and satisfaction Work to performance employee with long hours of work as intervening variables at PT. Coca Cola Amatil Indonesia (Central Java). Method research used​ is approach quantitative with technique data collection via distributed questionnaires​ to employees in the company with amount sample as many as 287 employees . Data analysis was carried out use technique analysis path (path analysis) for test connection direct or not direct between variables study . Research result show that motivation and satisfaction Work own influence positive and significant to performance employee . Besides That's a long time of work proven become reinforcing intervening variables influence motivation and satisfaction Work to performance employee . With So , company need notice factors motivation and satisfaction Work as well as considering the length of work employee in effort increase performance they . Study This give contribution for development theory management source Power people and practice in the field , esp in context industry drinks in Indonesia...